The effect of different acidic irrigation solutions on the pushout bond strength of root canal filling - Funda Fundaoğlu Küçükekenci (Tabriz University of Medical Sciences, 2023)
Background. This study investigated the effects of different acidic solutions used as the final irrigation on the push-out bond strength (PBS) of resin-based and bioceramic-based root canal sealers. Methods. 100 single root and canal human incisors were selected and decorated. Root canal shaping was done with ProTaper Next rotary files up to X4 and rinsed with 5 mL of 5.25% NaOCl between each file. Then, teeth were divided into five main groups according to the final irrigation (n=20). Group 1: glycolic acid; Group 2: phosphoric acid; Group 3: citric acid; Group 4: EDTA and group 5: saline. Then, each group was divided into two subgroups according to the canal sealer used (n=10). The groups filled with bioceramic-based sealer (bioserra) were named A, and the groups filled with resin-based sealer (AH Plus) were called B. PBS test was applied to one of the two samples obtained from the coronal third of each root. The data were statistically analyzed using a two-way analysis of variance and Tukey's HSD test (α=0.05). Results. Statistically, the highest PBS value was obtained in group 2A (4.81±0.03 MPa), which was irrigated with phosphoric acid and filled with bioserra, and the lowest PBS value was obtained in group 5B (1.10±0,03), which was irrigated with saline and filled with AH Plus (P<0.05). There was a statistical difference between all groups except group 1A and group 3A (P<0.05). Conclusion. The bioceramic-based root canal sealer (bioserra) bond strength is superior to resin-based (AH Plus). Phosphoric acid, glycolic acid, and citric acid can be an alternative to EDTA.